“Terpasung Tak Terasa” (Melihat Eksistensi Politik Perempuan HTI) - Zusiana Elly Triantini (Unisia, 2009)
Reformation has brought about various models of thought, including fundamentalist Islamicthoughts, one of them being Hizbut Tahrir Indonesia (HTI). HTI offers various conceptsthat are controversial, including the concept of khilafah as an alternative to thecollapsed political and governmental systems of Indonesia. One of its controversial conceptsis that of political role of women which is gender biased and combines sociologicaland theological domains. This paper reveals that such a bias is caused by the method ofinterpretation of texts, which is literal or textual, by which the texts have to be understoodas it is explicitly written, not implicitly. This tends to reject other understandings that arelogical and contextual, using historical interpretation.Keywords: reformation, HTI, women, gender-biased.